Por um fio: a resistência e os devires nos trabalhos de Cristina Carvalho - Carvalho, Clara Nogueira de (2019)
This research aims to contextualize, from the point of view of gender discourses, Cristina Carvalho’s place as a Paraíba born woman/contemporary artist. For that purpose, we bring considerations regarding her life trajectory and her insertion in the artistical ladscape of Paraíba. We sought to investigate the usage of textile material and techniques, such as the free embroidery, in her creative processes, as well as to discuss her poetical materiality and the use of the red color in her works. We brought also considerations over the historical “feminine production” of the textiles practices and we deal with the feminist issues inherently attached to the theme, seeking to understand how that has reverberated on the contemporaneity and in this particular artist’s work. The investigation is centered in the reading of three works by Cristina Carvalho: Carta 5575, O Carvalho and Palma 1940, which present as a common thread the philosophical concept of becoming. The metodology has a qualitative character, using bibliographical sources, oral history and image study.